Family support and low-purine diet compliance in patients with gout arthritis - Dina Nur Saputri; Siswati; Shanti Rosmaharani; Iin Noviana (Journal of Clinical Nursing Studies and Practice, 2025)
Compliance with a low purine diet in gout arthritis patients is still low, caused by lack of understanding of the patient, difficulty in changing diet, limited access to low purine foods, and lack of family support, so that patients are at risk of experiencing recurrence and complications that can reduce quality of life. The purpose of this study was to identify the relationship between family support and compliance with a low purine diet in gout arthritis patients at the Peterongan Health Center , Jombang Regency. The study design used correlational analytics with a cross-sectional approach. The independent variable was family support, the dependent variable was compliance with a low purine diet. The population of gout arthritis patients with a sample of 48 respondents with a purposive sampling technique. Data collection using a questionnaire. Statistical analysis using the Spearman Rho test. The results of the study showed a relationship between family support and compliance with a low purine diet in gout arthritis patients with ap value of 0.000. The family has an important role in encouraging compliance with a low purine diet in gout arthritis patients, the results of the study showed that aspects of instrumental and emotional support were very necessary